Record of the deep sea shrimp Pasiphaea alcocki (Wood-Mason & Alcock, 1891) (Crustacea: Decapoda: Pasiphaeidae) from the southwestern coast of India - Kuberan, G.; Chakraborty, Rekha Devi; Purushothaman, P.; Maheswarudu, G. (Zootaxa, 2018)
The present study provides a report on the rare occurrence of the deep sea caridean shrimp Pasiphaea alcocki (Wood-Mason & Alcock, 1891) from the southwest coast of India after three decades. Earlier this species was recorded from Indian waters at a depth range between 335 and 1732 m while the present specimens were obtained in the depth range of 200-300m from the commercial bottom trawlers operated off Sakthikulangara fishing harbour (8°56'60.78"N /76°32'34.27"E) off (8°56'60.78"N /76°32'34.27"E), Kerala from the southern region of Arabian Sea, India. The level of interspecies genetic divergence using COI and 16S DNA sequences of Pasiphaea sp from the United States, National Center for Biotechnology Information (NCBI) were observed. The present study reports the record of Pasiphaea alcocki with a morphological description along with DNA barcoding and supplements the existing knowledge on this deep sea shrimp from the southwest coast of India, which is mandatory to understand the role of this species in ecosystem functioning.